Tren Penelitian Transformasi Digital: Sebuah Analisis Bibliometrik dan Masa Depan Transformasi Digital di Indonesia - Dara Puspitasari; Hyronimus Rowa; Ika Sartika (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2025)
Digital transformation has become an increasingly prominent trend in the public sector, particularly within the context of government reform. In Indonesia, while the growth of e-government initiatives reflects a strong commitment to digital development, it has also resulted in the proliferation of tens of thousands of applications across government institutionsömany of which are overlapping, redundant, and fragmented. This fragmentation poses significant challenges to organizational performance and the efficiency of public service delivery. A growing public service sector in this digital era is intellectual property services, particularly trademark registration. Despite the increasing demand, trademark services receive the highest volume of negative user feedback. Key issues include a lack of transparency in the application process, prolonged processing times, and insufficient explanation for application rejections, leading to widespread user confusion and dissatisfaction. This study aims to analyze the research trends on digital transformation in the delivery of public services, with a specific focus on intellectual property services. A bibliometric analysis method is employed to map the evolution and scholarly focus on this subject. Findings suggest that Indonesia’s digital transformation remains in the digitization phaseöan early stage focused on shifting from analog to digital formats. For digital development to be impactful, it must evolve toward a meaningful digital transformation, which includes three strategic goals: building an inclusive, empowering, and trusted digital ecosystem. Achieving this requires stronger synergy and collaboration among all stakeholders, including government bodies, private sectors, academia, and civil society organizations.